IMPROVEMENT OF READING SKILLS THROUGH THE GAME’S CRAFTING TECHNIQUES ON GRADE 1 ELEMENTARY SCHOOL - Lilis Komariah; Anugrah Ramadhan Firdaus (IKIP Siliwangi, 2018)
This research aims to improve students reading skills through the application of the technique of composing words. This technique is a form of cooperative learning development that has characterized the developing activities thinking through discussion or group work. The subject of research is the grade 1 SDN 070 Pasirluyu, years 2017/2018 lesson. The research approach used is qualitative while the type of research that is a class act (CAR). Data analysis techniques using interactive model analysis technique consist of three components, namely the reductions of data, data and cereal drawdown conclusion. Based on a result of research that has been carried out can be concluded that crafting game techniques can improve the ability to read grade 1 SDN 070 Pasirluyu. It can be seen from the increase in the number of studying thoroughly in the percentage of the initial conditions that only 54% increased to 71% in cycle 1 and reach 92% the end of cycle 2. The total increase in the result of the study is of 46% yield close to average at this stage of pre-cycle of 58 rose to 71 in cycle 1 and cycle 2 be 87 on. pre-cycle.